Issues of the Significance of Co-Management in Production Conditions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the specific features, norms, and advantages of joint management in production settings, drawing on foreign experience. It highlights the need to align all elements of the emerging management system at the micro level in the context of Uzbekistan's digital economy and innovative technologies. The article discusses the importance of modern methods for evaluating organizational activities, including labor relations and indicators. It also compares the American and Japanese approaches to personnel management, emphasizing the significance of individual creativity and collective decision-making processes. The study suggests that adopting these international practices can enhance management effectiveness and foster high-performing teams in Uzbekistan's enterprises. Ultimately, the article calls for the application of modern personnel management methods to achieve better economic results.